Hygienic assessment of asbestos containing dust in the air of the working zone at thermal power plants. - V. E. Moshkovskiy (Medičnì Perspektivi)
Asbestos and artificial mineral fibers were used actively at thermal power plants (TPP) as heat insulation of pipes, seal plates, electrical insulation, etc. But content of asbestos fibers in the air of working zone at TPP was not registered to date. Therefore, aim of the work was to assess asbestos containing dust in the air of working zone at steam turbine and gas turbine TPP in the east region of the country.It was found that old insulation at TPP is mixture of asbestoses that contains chrysotile asbestos and traces of amphibole asbestoses – crocidolite and anthophyllite. In the majority of investigated workplaces at the steam turbine TPP significant dust generation with exceed of maximum one-time exposure limits (2 mg/m3) was observed. Concentration of respirable fibers in the air of working zone in all workplaces did not exceed actual hygienic standard (1 fiber/cm3).